Modifikasi Poros Dudukan Batu Gerinda Mesin End Mill Cutter Grinder di Bengkel Teknik Mesin Politeknik Negeri Medan - Handoko, Riki; Nasution, Hendra; Hutahaean, Naomi (Jurnal Inovasi Global, 2025)
End mill cutter is a type of blade that is commonly used in the working practice of milling machines. Because it is easily dull, these blades need to be sharpened to obtain a good geometric shape of the cutting surface. At the mechanical engineering workshop of the Medan State Polytechnic, the sharpening process is carried out using an end mill cutter grinder machine. However, the quality of the honed results is still not good. This study aims to improve the quality of the sharpening results by modifying the grinding stone stand shaft on the sharpening machine. The method used is a technical experiment by changing the dimensions of the shaft and locking system so that the grinding stone rotation becomes more symmetrical and stable. Primary data were obtained by measuring the symmetry of the mounting shaft with the indicator dial and the cutting experiment on the workpiece. Data analysis was carried out by comparing data from the old shaft with the new modified shaft. Sharpening experiments were carried out on the end mill cutter Ø 20 mm and the results obtained were very good cut quality and symmetrical tests showed a result of 0.055; 0.04 ; 0.01 mm is still below the standard tolerance of 0.05 mm.